Cassian the monk - Stewart, Columba (Oxford studies in historical theology., 1998)
This is a study of the life, work and spiritual theology of John Cassian (c.365-430) whose writings were the bridge between eastern monasticism and the developing Latin monasticism of Southern Gaul. He exerted a major influence on the rule of Benedict and the theology of Gregory the Great.